Comparative Morphometric Analysis of a Salinity-Tolerant Nile Tilapia (Oreochromis niloticus) Local Strain (Salina) and Its Parental Strains - Bawono, Yohanes Pamungkas; Dewi, Kiki Mariya; Romadhona, Ekky Ilham; Widantara, Handang; Sujatmiko, Wisnu; Aliah, Ratu Siti; Sutanti, Sutanti; Larassagita, Annisa Fitri; Firmansyah, Muhamad Kholik; Megawati, Novi; Aslia, Aslia; Ardiansyah, Arif Rahmat; Chaidir, Iding; Yaniharto, Dedy (Jurnal Medik Veteriner, 2025)
This study focuses on the morphology of the Nile tilapia local strain (Salina), a salinity-tolerant tilapia hybrid strain developed by crossbreeding between female Nile tilapia Red NIFI with male Nile tilapia Sultana. The research aimed to analyse the morphometric characteristics of the Salina strain to understand species adaptation to suboptimal environmental conditions compared with the parental groups. A total of 60 Nile tilapia fish, ten female and ten male samples from each strain (Salina, Sultana, and red NIFI), were measured for their total length (TL), standard length (SL), head length (HL), body width (WID), dorsal fin length (DL), caudal fin length (CL), pectoral fin length (PL), caudal peduncle depth (CPD), eye diameter (ED), snout length (SNL), and body weight (BW). Each measurement parameter was then normalized by comparing it with the standard length (SL). The data were analysed using MS Excel 2019 and R v4.5.1 for all statistical analysis including MANOVA, Canonical Variance Analysis, Principal Component Analysis, and Hierarchical Clustering Analysis. Condition factor (K) and length-weight relationship (LWR) were calculated to investigate growth conditions and allometric growth patterns, respectively. Based on the findings, the six tilapia populations exhibit overlapping morphological traits, except for female Salina with slight differences in morphological variations. This implies its potential unique traits acquired from crossbreeding between two different strains. Meanwhile, male Salina showed morphometric traits closely aligned with its male parent, the Sultana strain. The condition factor across all populations indicates favourable growth conditions, although the negative allometric growth pattern suggests that length increases more rapidly than body weight, implying an adaptive trade-off in suboptimal environments.